2019
DOI: 10.1055/s-0039-1687921
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Injury to the Lower Limb: Repair and Secondary Reconstruction

Abstract: This article is based on literature review of relevant articles as well as the authors’ own experiences in treating peripheral nerve injuries of the lower limb. The article deals with causative factors of lower limb nerve injuries, various grading systems of the injuries, approaches to such injuries, and techniques to repair lower limb nerve injuries. It also enumerates several reasons to explain the poorer prognosis of peroneal nerve injuries and the possible distal nerve transfers in lower limb albeit with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In UE nerve transfers are favored over other methods of nerve reconstruction i.e. nerve autograft, as it can avoid harvesting a nerve graft and provide an optimal chance of functional recovery [ 26 ]. Furthermore, studies have shown similar if not better results from nerve transfer compared to that of long nerve grafts.…”
Section: Reviewmentioning
confidence: 99%
“…In UE nerve transfers are favored over other methods of nerve reconstruction i.e. nerve autograft, as it can avoid harvesting a nerve graft and provide an optimal chance of functional recovery [ 26 ]. Furthermore, studies have shown similar if not better results from nerve transfer compared to that of long nerve grafts.…”
Section: Reviewmentioning
confidence: 99%
“…TMR has been established as a viable surgical option in the prevention and management of neuroma pain in both amputee and nonamputee patients. 6 , 13 By rerouting the sensory nerve endings to motor nerves in a nearby muscle, TMR directs nerve regeneration into the target muscle, which results in decreased neuroma formation and effectively alleviates residual limb pain and phantom pain in amputees. 5 , 6 This decreased pain corresponds with concomitant decreased rates of narcotic use.…”
Section: Discussionmentioning
confidence: 99%
“…Sciatic nerve injury (SNI) has the characteristics of high disability rate and di cult recovery of nerve function [1], and secondary lesions will spread to the surrounding normal tissues, resulting in chronic loss of function [2]. The etiology of secondary damage in SNI is not yet clear, but microcirculation disturbance is considered to be one of the important reasons for secondary damage [3][4][5].…”
Section: Introductionmentioning
confidence: 99%